Academic Stress of University of Muhammadiyah Sidoarjo Students Who Study While Working Class of 2021 - Willadul Musikhah; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the phenomenon of academic stress that occurs in college students while working. This study aims to determine the description of Academic Stress in Students Studying while Working Class of 2021 at Muhammadiyah University of Sidoarjo, with a total of 161 students as respondents. This type of research uses descriptive quantitative research methods. The data analysis process was carried out using SPSS version 17.0. The results of the reliability test on the academic stress scale showed a reliability coefficient of 0.898. The results of data analysis from academic stress research on students who are studying while working class of 2021 at Muhammadiyah University of Sidoarjo are classified as moderate with a percentage value of 66%. The results of this study also showed that the cognitive aspect of women had a higher score of 17.35%. So that students tend to have negative thoughts, and tend to be difficult to do assignments and difficult to concentrate